Relationship between Categorical Variables for widespread of Physical inactivity among University Students: A study - Anwar Ali; Mohammad Ahsan (Zien Journals, 2021)
Physical inactivity is a health concern that is considered a potential risk factor for adverse health outcomes worldwide. Potential barriers to physical inactivity should be identified and eliminated to promote active living and reduce inactivity among college students.
Keywords: Physical; concern; potential; inactivity